Effect of Mediterranean diet for pregnant women: a meta-analysis of randomized controlled trials. (17th December 2022) - Zhang, Yuan; Xia, Min; Weng, Shuangyan; Wang, Caixia; Yuan, Ping; Tang, Sisi
Abstract: Introduction: Mediterranean diet might be a promising approach to prevent gestational diabetes mellitus. However, the results remained controversial. We conducted a systematic review and meta-analysis to explore the effect of Mediterranean diet on gestational diabetes mellitus. Methods: PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases were systematically searched. Randomized controlled trials (RCTs) assessing the effect of Mediterranean diet on gestational diabetes mellitus were included. Meta-analysis was performed using random-effect model. Results: Four RCTs involving 2277 patients were included in the meta-analysis. Overall, compared with control intervention for pregnant women, Mediterranean diet was associated with reduced incidence of gestational diabetes mellitus (OR = 0.66; 95% CI = 0.52 to 0.82; p = .0003) and gestational weight gain (SMD = −0.15; 95% CI = −0.26 to −0.05; p = .004), but had no obvious effect on preeclampsia (OR = 1.04; 95% CI = 0.52–2.11; p = .91), preterm delivery (OR = 0.55; 95% CI = 0.20–1.55; p = .26) or neonatal unit (OR = 0.71; 95% CI = 0.43–1.19; p = .19). Conclusions: Mediterranean diet may be effective to prevent gestational diabetes mellitus.